Downstream Processing of Crude Ultrasound-Extracted Pectin From Saba Banana (Musa acuminata x balbisiana (BBB Group) “Saba”) Peel - Rachel S. Rodulfo; Katherine Ann T. Castillo-Israel; Prince Joseph V. Gaban; Ma. Cristina R. Ilano; Joshua B. Benedicto; Mark Anthony A. Badua; Joel P. Rivadeneira (International Journal of Food Science)
Ultrasound-assisted extraction of pectin from Saba banana (Musa acuminata x balbisiana (BBB Group) “Saba”) peels produced crude pectin that requires further purification. Two downstream processes (alcohol washing (AW) and acid demethylation (AD)) were compared. AW involved gelatinous precipitate washing with 85% alcohol and pressing to squeeze out liquids, while AD involved a sequential AW of the dried pectin with 60% acidified alcohol, and 60% and 95% alcohol solutions. Results showed that both methods produced low methoxyl pectins with similar color, yield, and moisture content, with no significant (p>0.05) differences observed. AD, however, produced pectin with better quality in terms of ash content and anhydrouronic acid (AUA) content relative to the control. Fourier transform infrared spectra revealed that the samples contain -OH, C-H, COO−, COO, and C-O groups, but only AD has COO-R due to structural modification. Overall, AD has the potential to improve the quality of crude ultrasound-extracted pectin from Saba banana peels. Yet, pre-extraction processing methods are necessary to meet FAO color standards for pectin.